Molecular mechanisms of HIF-1alpha modulation induced by oxygen tension and BMP2 in glioblastoma derived cells. - Francesca Pistollato (PLoS ONE, 2009)
BACKGROUND: Glioblastoma multiforme (GBM) is one of most common and still poorly treated primary brain tumors. In search for new therapeutic approaches, Bone Morphogenetic Proteins (BMPs) induce astroglial commitment in GBM-derived cells in vitro. However, we recently suggested that hypoxia, which is characteristic of the brain niche where GBM reside, strongly counter-acts BMP effects. It seems apparent that a more complete understanding of the biology of GBM cells is needed, in particular considering the role played by hypoxia as a signaling pathways regulator. HIF-1alpha is controlled at the transcriptional and translational level by mTOR and, alike BMP, also mTOR pathway modulates glial differentiation in central nervous system (CNS) stem cells. METHODOLOGY/PRINCIPAL FINDINGS: Here, we investigate the role of mTOR signaling in the regulation of HIF-1alpha stability in primary GBM-derived cells maintained under hypoxia (2% oxygen). We found that GBM cells, when acutely exposed to high oxygen tension, undergo Akt/mTOR pathway activation and that BMP2 acts in an analogous way. Importantly, repression of Akt/mTOR signaling is maintained by HIF-1alpha through REDD1 upregulation. On the other hand, BMP2 counter-acts HIF-1alpha stability by modulating intracellular succinate and by controlling proline hydroxylase 2 (PHD2) protein through inhibition of FKBP38, a PHD2 protein regulator. CONCLUSIONS/SIGNIFICANCE: In this study we elucidate the molecular mechanisms by which two pro-differentiating stimuli, BMP2 and acute high oxygen exposure, control HIF-1alpha stability. We previously reported that both these stimuli, by inducing astroglial differentiation, affect GBM cells growth. We also found differences in high oxygen and BMP2 sensitivity between GBM cells and normal cells that should be further investigated to better define tumor cell biology.